Photon‐in photon‐out hard X‐ray spectroscopy at the Linac Coherent Light Source. (14th April 2015) - Alonso‐Mori, Roberto; Sokaras, Dimosthenis; Zhu, Diling; Kroll, Thomas; Chollet, Mathieu; Feng, Yiping; Glownia, James M.; Kern, Jan; Lemke, Henrik T.; Nordlund, Dennis; Robert, Aymeric; Sikorski, Marcin; et al.
<x xml:space="preserve">Abstract</x> X‐ray free‐electron lasers (FELs) have opened unprecedented possibilities to study the structure and dynamics of matter at an atomic level and ultra‐fast timescale. Many of the techniques routinely used at storage ring facilities are being adapted for experiments conducted at FELs. In order to take full advantage of these new sources several challenges have to be overcome. They are related to the very different source characteristics and its resulting impact on sample delivery, X‐ray optics, X‐ray detection and data acquisition. Here it is described how photon‐in photon‐out hard X‐ray spectroscopy techniques can be applied to study the electronic structure and its dynamics of transition metal systems with ultra‐bright and ultra‐short FEL X‐ray pulses. In particular, some of the experimental details that are different compared with synchrotron‐based setups are discussed and illustrated by recent measurements performed at the Linac Coherent Light Source.